2021
DOI: 10.1002/ccr3.5196
|View full text |Cite
|
Sign up to set email alerts
|

Transverse myelitis after SARS‐CoV‐2 infection: Report of two cases with COVID‐19

Abstract: Transverse myelitis has been reported as a complication of COVID‐19 in recent studies. Here, we report two cases of transverse myelitis related to COVID‐19. Both patients underwent plasma exchange after being treated with antibiotics and corticosteroids which lead to the recovery of one of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Two potential proposed theories describe how SARS-CoV-2 may cause neurological complications such as Transverse Myelitis. The rst being through direct neuroinvasion in which SARS-CoV-2 infects the brain and spinal cord through its binding receptor, angiotensin-converting enzyme 2, ACE2 [3]. ACE2 receptors are most abundantly found in the lung cells leading to the upper respiratory manifestations most often seen in COVID-19 positive individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two potential proposed theories describe how SARS-CoV-2 may cause neurological complications such as Transverse Myelitis. The rst being through direct neuroinvasion in which SARS-CoV-2 infects the brain and spinal cord through its binding receptor, angiotensin-converting enzyme 2, ACE2 [3]. ACE2 receptors are most abundantly found in the lung cells leading to the upper respiratory manifestations most often seen in COVID-19 positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no single etiology of transverse myelitis, there have been numerous proposed etiologies, including paraneoplastic, autoimmune (perhaps due to multiple sclerosis or acute disseminating encephalomyelitis), and para-infectious causes (due to Herpes simplex virus or Mycoplasma pneumoniae) in which the body's response to the foreign pathogen mistakenly affects proteins in myelin. There have been few cases published regarding TM and COVID-19 as the complication is quite rare [3,4,5,6]. Here we present the case of a healthy, immuno-competent woman who developed a case of transverse myelitis after previously being infected with the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 93%
“…39 Case reports and review articles have reported COVIDÀ19-associated transverse myelitis with onset 7 to 21 days following COVIDÀ19 symptoms or diagnosis. [40][41][42] Nine out of 10 patients from these reports had spinal cord lesions that extended along three or more vertebrae without abnormal brain MRI findings (►Fig. 4).…”
Section: Transverse Myelitismentioning
confidence: 99%
“…4). [40][41][42] One patient had severe diffuse weakness and paraplegia with an extensive spinal cord lesion and without evidence of ADEM on brain MRI. 41 Given the postinfectious delay between infection and symptom onset, it has been suggested that COVIDÀ19-associated transverse myelitis is immune-mediated, possibly with pathophysiology similar to ADEM.…”
Section: Transverse Myelitismentioning
confidence: 99%
“…There are numerous proposed etiologies for TM, including paraneoplastic, autoimmune (perhaps due to multiple sclerosis or acute disseminating encephalomyelitis), and para-infectious causes (due to Herpes simplex virus or Mycoplasma pneumoniae) in which the body's response to the foreign pathogen mistakenly affects proteins in myelin. A few cases have been published regarding TM and COVID-19 as the complication is quite rare [ 5 - 10 ]. Here, we present the case of a healthy, immunocompetent woman who developed a case of TM after being infected with the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 99%